DRIP EDUCATION: TEACHING GRAMMAR - PARTS OF SPEECH TO UNDERGRADUATE STUDENTS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Drip Education means a method of delivering the learning lessons in a broken way. Drip content refers to gradually releasing course material over a specified period to increase the power of retention and application. It means continuous learning with a variety of related topics to convert students’ interest into a tangible action to achieve desired outcomes. Language is a human phenomenon. One must talk as conversation puts people at ease and in harmony with one another. Even a person is judged on the basis of his speech. English in particular is a lingua-franca of the world, and we should note that although it is called English it no longer has any necessary connection with England. It is not enforced by any authority, but is maintained as a standard, without effort, by the needs of commercial, literary, and scientific communication. So it is not just learning a language _it is learning the basis of all its future activities, this means by which it is going to learn almost everything else. Learning English will make you sapien. So the demand for fluency and proficiency is increasing day by day. To achieve this goal in an Indian context where English is a second language is always challenging. To meet the requirements of further up-gradation in practical use of English the present paper emphasizes the re-orientation of grammar; and its implementation in an effective way.To train the students up to the level to compete with students of developed countries is a great challenge. This immediate challenge is to improve language intelligibility. Testing is an important tool of evaluation. It helps to know the learner’s competency level so that remedial measures could be taken. To achieve the desired course objectives critical self-assessment of the learners by themselves is important. Word classes or parts of speech fall into two broad categories. The Open class (Lexical Words) &close Set of Words. The present study focuses on Open class words only, i.e. nouns, adjectives, verbs, adverbs.